Keeping and breeding the rescued Sunda pangolins (Manis javanica) in captivity. Issue 6 (17th November 2017) - Zhang, Fuhua; Yu, Jiaming; Wu, Shibao; Li, Shaoshan; Zou, Cuiyun; Wang, Qiaoyun; Sun, Ruyong
Abstract : The Sunda pangolin ( Manis javanica Desmarest, 1822) is a Critically Endangered species. Given that this species lacks effective policies for in situ conservation and prevention of poaching in the wild, ex situ conservation and a captive breeding program are urgently needed to save this species from extinction. However, techniques for the maintenance and captive breeding of pangolins have not been well developed. In June 2010, we established the Pangolin Research Base for Artificial Rescue and Conservation Breeding of South China Normal University (PRB‐SCNU). To date, a total of 34 Sunda pangolin cubs have been born at PRB‐SCNU, 26 of which were captive bred, indicating great progress in keeping and breeding the Sunda pangolin. The techniques for maintenance—including housing, transitioning to an artificial diet, husbandry, and captive breeding—are described in this paper. The purpose of this manuscript is to share our successful experiences and techniques in the maintenance, management, and captive breeding of Sunda pangolins, and to provide guidance and a reference for the captive care and management of Sunda pangolins and other pangolin species.